Asymmetric supercapacitors: An alternative to activated carbon negative electrodes based on earth abundant elements. (June 2019) - Rahmanifar, Mohammad S.; Hemmati, Maryam; Noori, Abolhassan; El-Kady, Maher F.; Mousavi, Mir F.; Kaner, Richard B.
Abstract: High power performance with the ability to be charged in a matter of seconds have made supercapacitors the technology of choice for cutting-edge applications. However, improving the energy content of supercapacitors is necessary to contribute to the technological advancement of energy storage devices. Herein, we report the synthesis of two transition metal spinel oxide-reduced graphene oxide (rGO) nanocomposites; namely CuCo2 O4 -rGO and CoFe2 O4 -rGO. The CuCo2 O4 -rGO nanocomposite as a positive electrode exhibits an extremely high specific capacitance of 2064.0 F g −1 at 2 A g −1, whereas the CoFe2 O4 -rGO nanocomposite as a negative electrode shows a specific capacitance of 261.0 F g −1 at 2 A g −1 . The asymmetric CoFe2 O4 -rGO//CuCo2 O4 -rGO device exhibits an ultrahigh specific energy of 77.2 Wh kg −1 at 953.0 W kg −1, maintains 8.3 Wh kg −1 under the outstanding specific power of 21.0 kW kg −1, and displays excellent cycling stability (96% capacitance retention after 5000 cycles). We also fabricated an asymmetric AC//CuCo2 O4 -rGO device (AC = activated carbon) as a control, and realized that the CoFe2 O4 -rGO nanocomposite not only outperforms AC in terms of specific energy, but also contributes to a higher specific power. The results indicate that these nanocomposites are promising materials for the fabrication of high performance supercapacitors. Graphical abstract: On the hunt for a negative electrode active material . Two new CoFe2 O4 -rGO and CuCo2 O4 -rGO nanocomposites, based on transition metal spinel oxides, showed great potential to be applied as negative and positive electrode active materials for a supercapacitor. CoFe2 O4 -rGO as a negative electrode active material better counterbalances the electrochemical performance of the positive one and opens new prospects for the design and fabrication of highly efficient supercapacitor devices.Image 1 Highlights: High performance active materials based on earth abundant elements are introduced. The CuCo2 O4 -rGO nanocomposite was introduced as a positive electrode (C = 2064 F g −1 @2 A g −1 ). The CoFe2 O4 -rGO nanocomposite was introduced as a negative electrode (C = 261 F g −1 @2 A g −1 ). The CoFe2 O4 -rGO//CuCo2 O4 -rGO device shows an ultrahigh specific energy (77.2 Wh kg −1 @953 W kg −1 ). The device charged up with an off the grid system that makes energy on-site.